PENGEMBANGAN SISTEM INFORMASI OLAH DATA APOTEK WAY KANAN BERBASIS WEB - Febi Eka Febriansyah; Lili Adiningsih (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
Waykanan pharmacy is a pharmacy that sells and has a large stock of medicines, this Waykanan pharmacy has many customers who come every day. The medicines data of this pharmacy is divided into three types of medicines, each of which includes tablets, capsules and syrups. All transactions in these pharmacies are still recorded manually, namely by recording these transactions into a book. Some of the transactions carried out included medicines sales transactions to consumers, both prescription and non-prescription sales. Information technology, especially the web, is one alternative to overcome the sale of these medicines. The purpose of this research is to produce a system that is able to record sales transactions and is able to enter medicines data and make reports. This study uses a prototype method and testing using UAT (User Acceptance Testing). The results of testing this system successfully run as it should and based on testing the level of user satisfaction on the pharmacy information system, the test results are in the good category with satisfaction levels of 79%, 77%, and 81% from each group of system admin testers, pharmacy owners and cashier. The large percentage means that the level of satisfaction of the pharmacy information system is in the very good category.